How Important Psychological Safety is in Supporting Strategic Management to Achieve Success: A Narrative Literature Review - Setya Negara, Ade Irma; M. Fachrizal Helmi; Ariesta Tohir Wijaya; Harries Madistriyatno (HM Publisher, 2023)
Psychological safety plays a crucial role in enhancing strategic management processes and outcomes. Psychological safety encourages open and honest communication among team members and leaders. When individuals feel safe to share diverse perspectives, it fosters the generation of innovative ideas, facilitates effective decision-making, and improves problem-solving capabilities within strategic management teams. Psychological safety cultivates a supportive and inclusive work environment. It encourages active participation and collaboration among team members, resulting in increased trust, stronger team cohesion, and improved overall team performance. Organizations can enhance their strategic management practices and ultimately achieve sustainable competitive advantage by creating an environment that promotes open communication, inclusivity, risk-taking, and employee well-being. Understanding and prioritizing psychological safety within the strategic management framework is crucial for organizations aiming to thrive in an increasingly complex and uncertain business landscape.